Studying the Factors Affecting on Use of Management Information Systems: Case Study - Tehran Municipality - Ghaderi, Sohrab; Faezi, Jafar Sadegh; Kahrizeh, Ali Amiramini (International Review of Management and Marketing, 2017)
This study aims to examine the factors affecting on use of management information systems (MIS) in 22 districts of Tehran municipality. This paper is practical by purpose and it is descriptive-survey in terms of method. It belongs to case study class among types of descriptive study methods. Field library approach is used for collecting information. Statistical population of this study includes 132 managers and assistants of Tehran municipality which are selected by convenient approach. Validity and reliability (Cronbach's alpha) of questionnaires suggest that measurement tool is of appropriate validity and reliability. Results are obtained from analyzing testing the hypotheses by SPSS.v.21 study and using one sample t test and Friedman test that environmental, organizational, and human factors are respectively the most important factors affecting on use of MIS in 22 districts of Tehran municipality. Keywords: ICT; human factors; environmental factors; organizational factors JEL Classifications: D83, L2